The search for wellbeing and health between the Middle Ages and Early Modern Period - Rider, Javier López (2024)
The Search for Wellbeing and Health between the Middle Ages and the Early Modern Period compiles a series of works on cosmetics and health care, covering different geographical areas of Europe. The studies also focus on different cultures, with some chapters dedicated to the Hebrew sphere, others to the Muslim world, and a larger percentage dealing with Christian society. The contributions make use of some very important written sources: recipe books and treatises on medicine and cosmetics, especially those preserved from the Late Middle Ages (13th-15th centuries) onwards. These manuscripts reveal the raw materials used to make certain products, whose origin could be vegetable, animal or mineral. Many were used to combat various ailments, but also to take care of the body aesthetically. Thus, there are remedies to heal the eyes; to avoid problems with the teeth and to make them shine white; creams and soaps for the skin; hair dyes to avoid grey hair; lotions to combat baldness; and even diverse gastronomic recipes to obtain inner wellbeing. Other contributions take a more practical perspective. Studies are included in which some of the ingredients and products are explored through experimental archaeology (chemical analysis) and faunal remains obtained from archaeological campaigns are analysed in the laboratory, showing the Christian diet. Overall the book demonstrates the importance of healthcare and cosmetics in past societies that had very significant technical knowledge of a multitude of completely natural and sustainable products.